Fundamental and Applied Scientific Research in the Development of Agriculture in the Far East (AFE-2021) Agricultural Innovation Systems, Volume 1 - Muratov, Aleksei; Ignateva, Svetlana (Lecture Notes in Networks and Systems, 2022)
XI, 689 p. 180 illus., 128 illus. in color.